The Effect of Exterior and Interior Roof Thermal Radiation on Buildings Cooling Energy. (2016) - Mohamed, Haider I.; Lee, Jeehwan; Chang, Jae D.
Abstract: Residential buildings in Iraq consume 42% of the country's total electricity production. As residential air-conditioning usage increases, so does the demand on the country's electrical power infrastructure resulting in more frequent power cuts and rolling blackouts. This research investigates the effectiveness of applying a reflective roof, radiant barrier and interior radiation control coating to reduce the space cooling loads of Iraqi houses and in turn electricity demand. Findings from this study's preliminary energy simulations indicate that external roof coatings, internal coatings, and radiant barriers can provide a significant reduction in cooling load compared to the typical roof finishes of Iraqi houses therefore potentially reducing the energy demand on the country's energy infrastructure.